Polyfurfural film modified glassy carbon electrode for highly sensitive nifedipine determination. (20th December 2015) - Zeng, Qiang; Wei, Tianyan; Wang, Min; Huang, Xinjian; Fang, Yishan; Wang, Lishi
ABSTRACT: A sensitive and convenient electrochemical strategy is developed for the determination of nifedipine basing on a polyfurfural film modified glassy carbon electrode (GCE) by the one-step electropolymerization of furfural. The prepared polyfurfural film/GCE exhibits excellent electrocatalytic activity towards nifedipine. A series of experimental parameters including the pH of supporting electrolyte, accumulation time and potential for nifedipine is also considered and optimized. Under optimal conditions, the proposed nifedipine sensor has a wide linear detection range from 1 × 10 −8 to 7 × 10 −6  mol dm −3, with a low detection limit of 5 × 10 −9  mol dm −3 . The proposed nifedipine sensor also displays excellent selectivity, stability and reproducibility. In particular, it shows splendid analytical performance for the determination of nifedipine in real pharmaceutical and human urine samples in practice.